Preliminary notes on the Census of Population in Northern Ireland, 1937 - Meenan, James (Statistical and Social Inquiry Society of Ireland, 1937)
The second Census of the Six Counties of Northern Ireland was taken on February 28th, 1937. The preliminary figures of that Census have now been published, and it will be of some interest to discover how far they disclose trends of population change which have been noted in the Census taken for the Free State area in 1936. Such an enquiry may be of greater interest since even the elementary statistics of the Six Counties are little known.
Barrington Lecture 1936/1937
Read on Friday, 28th May, 1937 - This lecture is delivered under the aupices of the Barrington Trust (founded by the bequest of John Barrington Esq.) with the collaboration of the Journal of the Statistical and Social Inquiry of Ireland.
Keywords: Northern Ireland Census 1937; Population count; 314.15